Evaluasi Pembelajaran Tematik Kelas Rendah MI. Miftahus Sa’adah Jakarta - Ina Magdalena; Jihan Saidatul Hasinah; Fildzah Dwi Oktari; Laila Febriyani Suteja (RC-INSTITUT, 2020)
This study is intended to describe (1) how the thematic learning evaluation in mi lower class of MI. Miftahus Sa'adah Miftahus Sa'adah 2) the teacher's obstacle to performing a thematic evaluation in the lower class of MI. Miftahus Sa'adah (3) the teacher's efforts to overcome the thematic evaluation in the lower class of MI. Miftahus Sa'adah. The study uses qualitative descriptive designs, the study subject being class I and III teachers. The object of this study is the way the teacher conducted the thematic evaluation of the thematic evaluation and the teacher's efforts to overcome the thematic evaluation in the lower class of MI. Miftahus Sa'adah. Data collection in this study uses observation and interview methods.